2009
DOI: 10.1103/physreva.80.063417
|View full text |Cite
|
Sign up to set email alerts
|

Photoassociation and coherent transient dynamics in the interaction of ultracold rubidium atoms with shaped femtosecond pulses. II. Theory

Abstract: Photoassociation of ultracold rubidium atoms with femtosecond laser pulses is studied theoretically. The spectrum of the pulses is cut off in order to suppress pulse amplitude at and close to the atomic resonance frequency. This leads to long tails of the laser pulse as a function of time giving rise to coherent transients in the photoassociation dynamics. They are studied as a function of cut-off position and chirp of the pulse. Molecule formation in the electronically excited state is attributed to off-reson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Subsequent experiments [24][25][26][27][28] observed coherent transients in excitedstate molecules photoassociated with femtosecond pulses and there was some evidence for the production of ground-state molecules [25]. In contrast, our approach is to control the dynamics of ultracold atoms at large R using nanosecondtime-scale frequency-chirped pulses.…”
Section: Introductionmentioning
confidence: 96%
“…Subsequent experiments [24][25][26][27][28] observed coherent transients in excitedstate molecules photoassociated with femtosecond pulses and there was some evidence for the production of ground-state molecules [25]. In contrast, our approach is to control the dynamics of ultracold atoms at large R using nanosecondtime-scale frequency-chirped pulses.…”
Section: Introductionmentioning
confidence: 96%
“…Early experiments demonstrated that the photodestruction of ultracold molecules could be coherently controlled using shaped [30] and chirped [31] ultrafast pulses. More recently, coherent transients were observed in excited-state molecules photoassociated with femtosecond pulses [32][33][34][35][36]. In addition, some evidence for the production of molecules in the electronic ground state was reported [33].…”
Section: Introductionmentioning
confidence: 98%
“…Apparently the time scale much shorter than the lifetime of the excited electronic state can overcome the losses caused by spontaneous emission. A frequency-domain cutoff and time-domain asymmetric laser pulses have been implemented to avoid atomic transition [18,19] and to maintain more photoassociated molecules caused by off-resonant excitation [20,21].…”
Section: Introductionmentioning
confidence: 99%